David Ohana. Albert Camus and the Critique of Violence. Trans. David Maisel. Brighton: Sussex Academic Press, 2017. - Melissa Ptacek (Studies in 20th & 21st Century Literature, 2018)
Review of David Ohana. Albert Camus and the Critique of Violence. Trans. David Maisel. Brighton: Sussex Academic Press, 2017. vi + 192 pp.
Keywords: Albert Camus; violence; humanism